Ludwik Silberstein on the Causality in Nature - Flin, Piotr; Stępień, Agnieszka (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2011)
In this paper we present the opinions of Ludwik Silberstein (1872-1948) on the question of causality in the scientiﬁc investigations. The discussion is based on the examples taken from physics and astronomy. Silberstein is convinced that the principle of causality is an important heuristic law, a diﬀerent kind of law of nature (as, for example, Kepler’s laws or Ohm’s law).